A new species of Dichelyne (Nematoda, Cucullanidae) parasitizing siaenid fishes from off the South American Atlantic coast - Timi, Juan Tomas (2009)
Anew nematode species Dichelyne (Cucullanellus) sciaenidicola sp. nov. is described based on specimens collected from the Whitemouth croaker Micropogonias furnieri (Desmarest) and the Argentine croaker Umbrina canosai Berg, from coastal waters of Argentina and Brazil. These nematodes were firstly identified as D. (C.) elongatus (Törnquist, 1931), a commonly reported species from M. furnieri in South American Atlantic waters. However, other species of Dichelyne have so far been reported from this host in the same area, namely D. (C.) rodriguesi (Pinto, Fábio et Noronha, 1970), D. (C.) amaruincai (Freitas, Vicente et Ibañez, 1969) and D. (Dichelyne) micropogonii Pereira et Costa, 1996. A careful re-examination of these parasites, as well as of type specimens of all species reported from M. furnieri, revealed that these nematodes represented a new species. The new species is distinguished from most of its congeners by having papillae 5-7 and 9 forming a subventral line close to cloaca, this feature is shared with other 6 species [D. (C.) dichelyneformis (Szidat, 1950), D. (C.) fraseri (Baylis, 1929), D. (C.) abbreviatus (Rudolphi, 1819), D. (C.) adriaticus (Törnquist, 1931), D. (C.) minutus (Rudolphi, 1819) and D. (C.) mariajuliae Alarcos, Timi, Etchegoin et Sardella, 2006)], which are readily distinguished by their body size, spicules length, distribution patterns of other papillae and position of the excretory pore and deirids. Also, D. (C.) elongatus from Umbrina canariensis (Valenciennes) from West Africa is established as a new species Dichelyne (Cucullanellus) yvonnecampanae sp. nov.; D. (C.) amaruincai from Pacific waters is considered as a valid species, D. (D.) micropogonii is regarded as species inquirendae and D. (C.) rodriguesi is identified as Cucullanus sp.